PENGARUH ENTREPRENUERIAL ORIENTATION DAN KAPABILITAS INOVASI TERHADAP KINERJA ORGANISASI: STUDI EMPIRIK PADA UKM KOTA SORONG - Reijeng Tabara; Uswatul Mardliyah (University of Riau Kepulauan, 2022)
The purpose of this study was to determine the effect of Entrepreneurial Orientation and Innovation Capability on organizational performance. The study used Structural Equation Modeling (SEM) through Partial Least Squares (PLS 2.0M3) to analyze 100 SMEs in Sorong City. The results of the study indicate that there is a positive and significant influence between Entrepreneurial Orientation on the performance of SMEs with a T-statistic value of 6.087 which is greater than T-table 1.660 at a significance level of 5% (0.05), Innovation Capability shows a positive and significant effect on the performance of SMEs with a T value -Statistic 3.471 is greater than T-table 1.660 at a significant level of 5% (0.05). The results of this study indicate that the higher the entrepreneurial orientation and the innovation capability that is built, the higher the performance of SMEs in Sorong City